Sustaining Quality Assurance Under Financial Constraints: A Study of Public and Community Colleges in Nepal - Gautam, Tara Prasad; Mishra, Anjay Kumar; Shailashri , V T (International Research Journal of Parroha, 2025)
This systematic review investigates the impact of financial constraints on quality assurance (QA) implementation and sustainability in Nepalese public and community colleges. Following PRISMA 2020 guidelines, a comprehensive search of databases identified 15 studies meeting inclusion criteria, which were analyzed using thematic synthesis and appraised with CASP and GRADE tools. Findings reveal that chronic underfunding, policy and governance weaknesses, limited faculty support, and low stakeholder engagement significantly hinder QA progress. The review aligns these challenges with Nepal’s National Education Policy 2019 and University Grants Commission reforms. Recommendations include increasing public investment, establishing dedicated QA funds, enhancing faculty capacity, enforcing policies, and promoting a culture of continuous improvement. The study highlights gaps for future research, particularly longitudinal evaluations and innovative financing models, to strengthen QA systems under financial constraints in Nepal and similar contexts.